Constitutional documents of the United States of America, 1776-1860 : supplement, Hawai'i and Liberia - Stauffer, Robert B.; Dunn, D. Elwood; Leitner, Miriam (K.G. Saur, 2008)
The six volumes of the German Constitutional Documents encompass more than 100 texts from Napoleonic times to the St. Paul's Church Constitution of 1849. They are published as part of the series entitled Constitutions of the World from the late 18th Century to the Middle of the 19th Century, a unique source edition that includes a complete collection of authentic historical constitutional texts for the period in question, all of which are annotated and indexed. Volume IV contains 26 constitutional documents for individual German states arranged in alphabetical and chronological order, from H.
Keywords: Constitutional law -- Hawaii.; Constitutional history -- Hawaii.; Constitutional law -- Liberia.; Constitutional history -- Liberia.; Droit constitutionnel -- Hawaii.; Histoire constitutionnelle -- Hawaii.; Droit constitutionnel -- Liberia.; Histoire constitutionnelle -- Liberia.; LAW -- Constitutional.; LAW -- Public.; Constitutional history; Constitutional law; Hawaii; Liberia; USA -- Verfassung -- Geschichte 1776-1861 -- Quelle -- Verfassung -- Geschichte 1789-1850